KEMANFAATAN PROGRAM/KEGIATAN PEMBANGUNAN DI KOTA JAYAPURA - Marsi Adi Purwadi (Universitas Cenderawasih, 2017)
In general, the objective of the study is to analyze the impact of development through physical activities undertaken by Jayapura City Government in 2015 against beneficiaries. The method used is an explanatory analysis. Quantitative descriptive statistical research into the form of measures of concentration, frequency distribution, cross tab analysis. Based on the results from the evaluation of programs / activities undertaken by Jayapura City Government in 2015, it can be concluded that: (1) The median financial and bodily realization through the use of local government budgets in 2015 is quite good because the realization of more than 93 percent ; (2) The General Allocation Fund is the largest source of funds used by Jayapura City Government in the implementation of development through bodily activities in 2015; and (3) The mean community assessing the implementation of development through programs / activities undertaken by the Jayapura City Government through DAK, DAU, DAU / DAK, DID and OTSUS Fund has been optimally and felt useful by the community. While only a small percentage of respondents stated that programs / activities undertaken by the local government have not been beneficial to the improvement to the community economy in Jayapura City. Keywords: development evaluation, program / activity benefit